Analysis The Effect Of Work Commitment And Job Satisfaction On Employee Performance At PT Bank Sulteng - M. Adharry Dwiki Syaputra Amran (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
Employee performance has become a crucial factor affecting organizational sustainability and competitiveness, particularly in the banking sector where service quality and productivity are highly dependent on human resources. Work commitment and job satisfaction have been recognized as important factors influencing employee performance; however, empirical findings remain inconsistent, particularly in regional banking institutions. This study aims to examine the effect of work commitment and job satisfaction on employee performance at PT Bank Sulteng. This study employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to employees of PT Bank Sulteng using a five-point Likert scale. The study involved 109 respondents selected through simple random sampling. Data were analyzed using multiple linear regression with IBM SPSS version 26, including validity, reliability, and classical assumption tests. The findings revealed that work commitment and job satisfaction positively and significantly affected employee performance both partially and simultaneously. The coefficient of determination indicated that both variables explained 52.4% of employee performance variation. Strengthening employee commitment and improving job satisfaction may significantly contribute to enhancing employee performance in banking institutions.